Deteksi Ektoparasit pada Ikan Nila (Oreochromis niloticus) di Balai Benih Ikan (BBI) Desa Aik Bukak Kecamatan Batukliang Utara Kabupaten Lombok Tengah - Arsyad, Nurlaela Sagita; Atma, Candra Dwi; Dharmawibawa, Iwan Doddy; Rahmawati, Septyana Eka (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Tilapia (Oreochromis niloticus) is one of the most widely cultivated freshwater fish in Indonesia, due to its high consumption rate and ease of maintenance. However, ectoparasite infection is a serious threat to fish health and productivity. This study aims to identify the presence and types of ectoparasites in Tilapia at the Fish Seed Center (BBI) of Aik Bukak Village, North Batukliang District, Central Lombok Regency. A total of 20 Tilapia samples from five parent ponds were examined using native scraping and biopsy techniques. The results of the analysis at the Histology and Pathology Laboratory, Faculty of Veterinary Medicine, Mandalika Education University, showed that 18 of the 20 samples were infected with ectoparasites. Morphological identification showed two types of parasites, namely Gyrodactylus sp. (Monogenea) and Trichodina sp. (Protozoa), which were found on the gills, mucus, and scales of the fish. These results indicate that ectoparasites are still a major problem in Tilapia cultivation at the research location.